Analysis of resistance to fatigue between straight solid and anatomic abutments of Morse taper system - Vanessa Tavares de GOIS-SANTOS; Cleverson Luciano TRENTO; Silvando Vieira dos SANTOS; Renan Celestino Silva SANTOS; Victor Santana SANTOS; Sandro GRIZA
Abstract Background The study of the phenomenon of fatigue is essential because implant failures usually are caused by this process. Purpose The objective of this study was to examine the fatigue resistance of straight and anatomical abutments joints that were submitted to cyclic loads. Material and method We used 37 Morse taper implants and 37 abutments, divided into two groups (n= 16: straight abutment, n= 21 anatomical abutment). The sets were submitted to cyclic loading (5 million) using servo-hydraulic equipment. Three sets from each group were subjected to bending tests to determine the maximum load resistance, which served as the parameter for comparison of the cyclic tests. We evaluated number of cycles, load and bending moment. Result Of the 31 abutments cyclically tested, 17 (54.8%) fractured in fewer than 5 million cycles; 8 (25.8%) of these were straight abutments, and 9 (29%) were anatomical. A total of 14 samples (45.2%) resisted the cyclic loading. According to Fisher's exact test, there was no difference between groups as the fracture. Conclusion Despite of the straight abutments have higher average load and bending moment on the anatomical, both types of abutments showed similar performance as the fracture strength in vitro.